Pengaruh penggunaan fintech (e-wallet) terhadap minat masyarakat dalam pembayaran online akibat pemberlakuan pembatasan kegiatan masyarakat - Nelyumna Nelyumna; Amelia Oktrivina; Adindafi Kartika Salwa (LPMP Imperium, 2022)
The increasingly large spread of the Covid-19 virus has made the government issue a regulation to limit people's activities outside the home, affecting people to use online services. Financial Technology (FinTech) is a financial service solution that utilizes digital technology in its operation, and Financial Technology can help people buy necessities without having to meet with sellers. The purpose of this study was to determine (1) the effect of perceived benefits on interest in using FinTech (e-wallet), (2) the effect of perceived convenience on interest in using FinTech (e-wallet), and (3) the effect of perceived risk on interest in using FinTech (e-wallet). The population in this study is the Jabodetabek community. The research method used is quantitative. The data used are primary data using a questionnaire filled out by respondents with a sample of 100 people. The analysis technique used in this research is using a multiple linear regression test. The results of this study indicate that: (1) There is a positive and significant effect of perceived benefits on interest in using FinTech (e-wallet), and (2) There is a positive and significant effect of perceived ease of use on interest in using FinTech (e-wallet), (3) There is a negative and insignificant effect of perceived risk on interest in using FinTech (e-wallet).